Pengaruh Diposisi Lapisan Tipis Tin Pada Ujung Mata Bor Terhadap Laju Pengeboran Pada Bahan Baja Karbon Rendah - Perpustakaan UGM, i-lib ([Yogyakarta] : Unit Informasi Inovasi Proses Pembelajaran (UI2P2) Universitas Gadjah Mada, 2003)
Enhancing performance of a drill bit can be performed by taking improvement into material hardness characteristics. This will be done by depositing a TiN thin layer within implantation time variable using accelerator. Implanted ions will be collided with electrons and atoms target. Once they are loosing their energy, they will he settled within material target and actuallv change materials properties.: The aim 1.4 this research: is to â¢ gain investigation of the effect of TiN thin layer deposition on a drill bit related to the drilling rate which is closely influenced production rate in manufacturing areas. Empiricalï´ method then would, be â¢ used to compare hardness gained from metal implantation with one without ion implantation. Samples from .i.wrioys'aiumete,-svere 'implanted within different time implantation. The sample with highest har dneis. number' then could be determined as a maxinuon.hardnesswith optimum time-variable. Eventually, the optimum time variable was used ai an implantation tithe to iinplant drill bits for drilling rate analYsis. -â¢ Risults of the reSearch'showedthatton implantation had-"strong effect into increasing drilling rate. These could also be summarizedthat drilling' rate has positif correlation with axial load in drilling process. â¢ - â Key words: aeolerator. implantation. TiN, thin layer deposisition, drilling rate